Two Birds with One Stone: Metal–Organic Framework Derived Micro‐/Nanostructured Ni2P/Ni Hybrids Embedded in Porous Carbon for Electrocatalysis and Energy Storage - Liu, Xiaobin; Li, Wenxin; Zhao, Xudong; Liu, Yongchang; Nan, Ce‐Wen; Fan, Li‐Zhen (Advanced functional materials, 2019)
The construction of bifunctional electrode materials for hydrogen evolution reaction (HER) and lithium‐ion batteries (LIBs) has been a hot topic of research. Herein, metal–organic frameworks (MOFs) derived micro‐/nanostructured Ni2P/Ni hybrids with a porous carbon coating (denoted as Ni2P/Ni@C) are prepared using a feasible pyrolysis–phosphidation strategy. On the one hand, the optimal Ni2P/Ni@C catalyst exhibits superior HER performance with a low overpotential of 149 mV versus a reversible hydrogen electrode (RHE) at 10 mA cm−2 and excellent durability. The density functional theory computations verify that the strong synergistic effect between Ni2P and Ni could optimize the electronic structure, thus rendering the enhanced electrocatalytic performance. On the other hand, the Ni2P/Ni@C electrode displays a reversible capacity of 597 mAh g−1 after 1000 cycles at 1000 mA g−1 and improved rate capability as an anode for LIBs, owing to the well‐organized micro‐/nanostructure and conductive Ni core. In addition, the electrochemical reaction mechanism of the Ni2P/Ni@C electrode upon lithiation/delithiation is investigated in detail via ex situ X‐ray powder diffraction and X‐ray photoelectron spectroscopy methods. It is expected that the facile and controllable approach can be extended to fabricate other MOF‐based metal phosphides/metal hybrids for electrochemical energy storage and conversion systems. Metal‐organic framework derived micro/nano‐structured Ni2P/Ni hybrids with a porous carbon coating are successfully prepared. As hydrogen evolution reaction catalysts, both experimental and computational results verify that the strong synergistic effect between Ni2P and Ni renders an enhanced electrocatalytic performance. As anode for Li‐ion batteries, the well‐organized micro/nano‐structure and the conductive Ni core jointly promote the electrochemical reaction kinetics.